2015
DOI: 10.3109/14397595.2015.1059984
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of a new triple combination treatment utilizing methotrexate, salazosulfapyridine, and bucillamine in rheumatoid arthritis

Abstract: The triple DMARD combination therapy provided a new treatment option for those patients for whom treatment with biologics is difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…EULAR recommendations are thought to have a sound therapeutic basis for abiding strictly to the T2T strategy. Indeed, recent studies have reported excellent results of triple DMARD therapy that is equivalent to that seen with bDMARDs [De Jong et al 2014;Karlsson et al 2013;Moreland et al 2012;O'Dell et al 2013;Matsuno et al 2016]. However, evaluation of the results of triple therapy must be cautious because the prevalence of discontinuation of treatment is higher in triple therapy than combination therapy of MTX plus bDMARDs according to Moreland and colleagues (37% versus 30%) [Moreland et al 2012] and Karlsson and colleagues (26% versus 10%) [Karlsson et al 2013].…”
Section: Which Combination Therapies Are Available?mentioning
confidence: 99%
“…EULAR recommendations are thought to have a sound therapeutic basis for abiding strictly to the T2T strategy. Indeed, recent studies have reported excellent results of triple DMARD therapy that is equivalent to that seen with bDMARDs [De Jong et al 2014;Karlsson et al 2013;Moreland et al 2012;O'Dell et al 2013;Matsuno et al 2016]. However, evaluation of the results of triple therapy must be cautious because the prevalence of discontinuation of treatment is higher in triple therapy than combination therapy of MTX plus bDMARDs according to Moreland and colleagues (37% versus 30%) [Moreland et al 2012] and Karlsson and colleagues (26% versus 10%) [Karlsson et al 2013].…”
Section: Which Combination Therapies Are Available?mentioning
confidence: 99%
“…Six of the eight patients without flare received intensified csDMARD therapy. The usefulness of triple-combination therapy for inducing remission has been previously reported ( 11 , 12 ). Kurasawa et al reported the efficacy of adding another csDMARD to reduce the flare rate after the discontinuation of IFX ( 6 ).…”
Section: Discussionmentioning
confidence: 94%
“…Since the effects of csDMARDs appear more slowly than those of MTX+TNF inhibitors, the clinical response of the triple therapy was comparable to that of MTX+TNF inhibitors, except for the fact that there were some differences in the degree of joint destruction (17, 18). It should be noted that the findings of O'Dell's and Matsuno's studies did not indicate that the effects of csDMARDs appear more slowly than those of MTX+TNF inhibitors (19, 20). In our study, we used ADA with MTX and increased the number of csDMARDs, with the aim of administering triple csDMARD therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Another reason for the good results regarding the numbers of patients who could achieve a Bio-free condition in our study may be the use of csDMARDs other than MTX. There have been reports of triple therapy with csDMARDs, and the clinical results were as good as those obtained with MTX+TNF inhibitors (17-20). Since the effects of csDMARDs appear more slowly than those of MTX+TNF inhibitors, the clinical response of the triple therapy was comparable to that of MTX+TNF inhibitors, except for the fact that there were some differences in the degree of joint destruction (17, 18).…”
Section: Discussionmentioning
confidence: 94%